A Periodic Solution of the Generalized Forced Liénard Equation. (18th June 2014) - Goodarzi, Zahra; Razani, Abdolrahman
Abstract : We consider the generalized forced Liénard equation as follows:( ϕ p ( x ′ ) ) ′ + ( f ( x ) + k ( x ) x ′ ) x ′ + g ( x ) = p ( t ) + s . By applying Schauder's fixed point theorem, the existence of at least one periodic solution of this equation is proved.